MIGRAÇÃO, ESTABILIZAÇÃO E SATURAÇÃO DE CARBONO EM SISTEMAS DE MANEJO DO SOLO EM REGIÃO SUBTROPICAL E TROPICAL - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2015)
No till system (NT), associated to crop rotations with high and varied residues input, has been a very important tool to restore the soil organic carbon (C) stock depleted by long-term soil tillage, like conventional till (CT). However, there is no clear understanding about the potential to soil accumulate C, especially for high weathered soils. It was hypothesized that continuous residue input and less macroaggregation turnover in NT promote greater C accumulation and stabilization, which is the direction to reach the C saturation potential. Furthermore, it was hypothesized that SOC-poor deep soil layers have greater potential to extra C accumulation than at surface layers, and that the nutrient scarcity could be a drive force to C accumulation in subsoil. Therefore, the objectives of this study were: (i) improve the knowledge regarding the mechanisms that govern the C stabilization in different tillage systems (NT vs. CT) and the potential to these tillage systems accumulate C; (ii) evaluate the C stabilization in soil layers with different C saturation deficits and; (iii) assess the C-residue migration into soil organic matter (SOM) fractions in a laboratory incubation experiment. Results showed greater C accumulation in NT than that in PC, both in labile and bound to minerals SOM fractions. Additionally, the bound to minerals SOM fraction fitted to saturation model (asymptotic) for all three sites and indicated that actual soil C is far from the estimated potential to C accumulation. The incubation experiment showed greater CO2-C emission in the 0-20 than that in the 40-100 cm layer. It was related to greater labile SOC, and better fertility attributes in the surface layer, which promoted greater microbial activity. Besides, the C-residue conversion into soil C was greater in the surface soil layer, indicating that the soil microbiota in this layer was more efficient in C cycling. The low pH and the nutrient scarcity of P, Ca2+ e Mg2+ in the 20-40 and 40-100 cm layer were the driving force decreasing microorganism activity and thus, limiting C conversion in deep soil layers. Labile SOM fraction had greater accumulation in the 0-20 cm layer, as a response to a smaller C saturation deficit in this layer. However, C in bound to minerals SOM fraction was specially accumulated in the 20-40 and 40-100 cm layers, indicating that C saturation deficits in deep soil layers stimulate C accumulation in more stabilized SOM fractions. All three sites showed high C accumulation capacity, and the C saturation in the SOM fraction bound to mineral for all 0-20 cm layer will be in 104, 103 and 63 years for Ponta Grossa, Londrina and Lucas do Rio Verde, respectively. Overall sites, C accumulation potential followed: native vegetation > NT > CT.
CARBON MIGRATION, STABILIZATION AND SATURATION IN TILLAGE SYSTEMS FROM SUB- AND TROPICAL REGIONS
Keywords: déficit de saturação de C; fracionamento da MOS; incubação; matéria orgânica do solo; plantio direto; saturation deficit; SOM fraction; incubation; soil organic matter; no till; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA